Kontrola kardiovaskulárních rizikových faktorů u diabetiků 2. typu - Petrlová, B; Rosolová, H; Simon, J; Sefrna, F; Sifalda, P; Sípová, I (Vnitrni lekarstvi, 2009)
The control of basic cardiovascular risk factors was examined in a sample of 415 diabetes type 2 patients, aged 66 +/- 10 years, with a 9.4 +/- 8 years long history of diabetes, both genders represented proportionally; 95% of the sample were hypertensive. The recommended blood pressure value was achieved by 13% males and 17% females. Antihypertensive monotherapy was indicated in 40% of the sample. Renin-angiotensin-aldosteron system inhibitors were prescibed to 90% of the sample. The fasting glycaemia < or = 6 mmol/L were achieved in 10% males and 11% females; glycosilated hemoglobin < 4.5% in 20% males and 24% females; 60% of the sample had antidiabetic pharmacotherapy--44% males and 48% females used metformin. Total fasting plasma cholesterol < 4.5 mmol/L was achieved in 31% males and 23% females; LDL-cholesterol < 2.5 mmol/L was achieved in 31% males and 41% females. The target values for diabetics in secondary prevention of cardiovascular diseases or with subclinical atherosclerosis was achieved in 13% of the sample. Statins were prescribed in 60% of the sample, fibrates in 4%. Only 2 females achieved all the target values. Hypolipidemic and antihypertensive drug therapy is unsatisfactory; there is certainly a big potential in life style changes among the diabetic patients.
Keywords: Diabetes Mellitus, Type 2; Female; rizikové faktory; Aged; kardiovaskulární nemoci; Humans; ženské pohlaví; Cardiovascular Diseases; mužské pohlaví; senioři; lidé; diabetes mellitus 2. typu; lidé středního věku; Male; Middle Aged; Risk Factors